Contextual teaching and learning assisted by E-modules: Enhancing mathematical communication ability and learning motivation on the Pythagorean Theorem - Meri Meri; Endang Wahyuningrum; Sudirman Sudirman; Ebenezer Bonyah (Nashir Al-Kutub Indonesia, 2026)
This study examined the effect of Contextual Teaching and Learning (CTL) assisted by an electronic module (e-module) on Grade VIII students’ mathematical communication ability and learning motivation in the Pythagorean Theorem. A quantitative quasi-experimental approach with a Nonequivalent Control Group Design involved 64 students at SMP Negeri 08 Tanjung Jabung Barat, Indonesia, divided equally into experimental and control classes (n = 32 each). The experimental class received e-module-assisted CTL across eight meetings, while the control class received conventional instruction. Data were collected using a mathematical communication essay test and a 32-item motivation questionnaire, both demonstrating high reliability (Cronbach’s alpha = 0.917 and 0.881). Baseline testing indicated no significant differences between groups in communication ability or motivation. After treatment, the experimental class achieved a significantly higher mathematical communication mean (82.42) than the control class (70.31), t(62) = 6.16, p < 0.0001, with a large effect (d = 1.54). A Mann–Whitney U test also showed significantly higher motivation in the experimental class (median = 88.00) than the control class (median = 78.00), Z = 6.87, p < 0.0001, r = 0.86. The experimental class also demonstrated substantially greater gains in both outcomes across the intervention period overall. These findings indicate that e-module-assisted CTL effectively enhances students’ mathematical communication ability and learning motivation, providing a practical technology-integrated alternative for junior secondary mathematics instruction.